Analisis Struktur Kekuatan Persaingan dan Cluster Industri - Eka Virgiawan Listanto; Fitriana Dewi Oktaviani Silaen; Muhammad yasin (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Industry clusters, which consist of a group of companies related geographically and sectorally, have become the focus of attention in regional economic and business strategy studies. This study uses an industrial structure analysis approach to understand the strength of competition within an industry cluster. Some of the factors analyzed include the level of industry concentration, new entries, bargaining power of buyers and suppliers, as well as product or service substitution. The data used in this study includes information about the companies that are members of the industrial cluster studied. The research method used includes secondary data collection, such as company financial reports, industry data, and related publications. In addition, interviews with industry stakeholders were also conducted to gain deeper insights into the structure of competitive forces and the factors that influence industrial clusters. The results of the analysis show that the structure of competitive forces in industry clusters can vary depending on the industrial sector studied. This research contributes to our understanding of how the structure of competitive forces and industry clusters can shape a competitive business environment, as well as providing useful insights for the development of effective business strategies within industry clusters.